Relationship between genetic and environmental characteristics of Lithuanian populations of purple loosestrife (Lythrum salicaria) - Jocienė, Lina; Krokaitė, Edvina; Shakeneva, Dinara; Rekašius, Tomas; Stanys, Vidmantas; Šikšnianienė, Jūratė B.; Žvingila, Donatas; Paulauskas, Algimantas; Kupčinskienė, Eugenija (Journal of Environmental Engineering and Landscape Management, 2022)
The present study evaluated genetic diversity of Lithuanian populations of Lythrum salicaria in relation to parameters of riparian environment. Growing along Nemunas, Seaside and Lielupė river basins, 15 populations were examined using amplified fragment length polymorphism markers. Molecular data were related to the river basins, type of land use and cover, natural vice versa regulated fragments of the rivers. Population mean genetic diversity parameters were as follows: percentage of polymorphic loci (57.2), expected heterozygosity (0.183), polymorphismc information content (0.218). Mantel test revealed correlation (R2 = 0.0986, p = 0.01) between genetic and geographic distance of populations. Greater genetic diversity within, rather than among populations (ΦPT = 0.213) was observed. According to the Bayesian clustering, studied populations are admixtures of two gene pools. Analysis of molecular variance revealed significant differentiation between populations belonging to distinct river basins, between populations from natural vs. regulated fragments of the rivers.